Dinamika Cinta Di Dunia Maya: Sebuah Interpretative Phenomenological Analysis Pada Dewasa Awal Yang Menjalin Cyber Romantic Relationship - Augusta, Dhiya Ayu Zahisyah; Susilawati, Luh Kadek Pande Ary (Peneliti.net, 2024)
Having romantic relationship can now be done virtually which is known as Cyber Romantic Relationships (CRR). The Covid-19 pandemic and the technology advances have driven an increase in the use of online dating apps that making CRR a phenomenon in society. Love serves as the foundation of romantic relationships. When it comes to expressing love in CRR, individuals face unique challenges. This research aims to understand the love dynamics of early adulthood who are in CRR and explore the factors influencing love in CRR. The respondents of this research are five early adult who are currently in Cyber Romantic Relationships. The method used in this research is qualitative with a phenomenological approach. Result shows five main themes: 1) Initial experiences of getting to know each other, this theme also encompasses the factors that drive individuals to fall in love virtually. These factors include physical appearance, compatibility in communication, shared interests and thoughts, also the partner’s personality. 2) Communication dynamics in CRR. 3) Issues in CRR. 4) Three components of love dynamic, namely: enchamcing partner well-being and mutual respect (intimacy), expressing affection through chat and call (passion), and also commitment, both short-term and long-term aspects.